The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1055/s-2008-1073128
|View full text |Cite
|
Sign up to set email alerts
|

Increased Aldosterone Levels in a Model of Type 2 Diabetes Mellitus

Abstract: In ZDF rats, urinary and plasma aldosterone levels were elevated despite reduced plasma renin activity. The reversible effect of ACE-inhibition shows that the up-regulation of aldosterone must be dependent of the renin-angiotensin-system in this type II diabetes model. The correlation between aldosterone and diabetic nephropathy suggests a clinical relevance of this observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 17 publications
3
18
1
2
Order By: Relevance
“…In addition, our study demonstrated significant elevation of plasma aldosterone in ZDF rats (supporting a compromised cardiovascular function and cardiac distress), but no further elevation of this hormonal biomarker of HF in response to RGZ treatment of ZDF rats was noted (Fig. 4), Table 1 which is in agreement with a previous report (Fredersdorf et al, 2009). Inflammation is another important cardiovascular risk, which is also known to be associated with MI-induced HF (Kherani et al, 2004).…”
Section: Discussionsupporting
confidence: 82%
“…In addition, our study demonstrated significant elevation of plasma aldosterone in ZDF rats (supporting a compromised cardiovascular function and cardiac distress), but no further elevation of this hormonal biomarker of HF in response to RGZ treatment of ZDF rats was noted (Fig. 4), Table 1 which is in agreement with a previous report (Fredersdorf et al, 2009). Inflammation is another important cardiovascular risk, which is also known to be associated with MI-induced HF (Kherani et al, 2004).…”
Section: Discussionsupporting
confidence: 82%
“…An association has been demonstrated in animal models between elevated aldosterone, type 2 diabetes, and the development of diabetic nephropathy (31). This finding in combination with our previous work showing a significant prevalence of microalbuminuria in adolescents with type 2 diabetes (12) suggests that aldosterone receptor blockade may have an important role in the treatment of hypertension in this patient population.…”
Section: Discussionsupporting
confidence: 75%
“…In adrenal tissue, Fredersdorf et al demonstrated increased levels of aldosterone in diabetic animals. 47 These results could be related to augmented activity of ACE both in kidney and adrenal tissue, which could enhance the amount of AII with stimulation of the production of aldosterone. However, it is important to emphasize that the size of the gland represents a limiting factor for assessing the concentration of angiotensin peptides present in the tissue.…”
Section: Figurementioning
confidence: 99%